Pretreatment with vincristine attenuates haematological and plasma biochemical alterations in isoprenaline treated rats (Nigerian Journal of Physiological Sciences, 2025)
Sustained adrenergic stimulation is linked to altered plasma biochemistry and haematological functions. However, whether vincristine, a vinca alkaloid with acclaimed cardioprotective property, can protect against biological alteration remains unknown. Hence, this present study investigated the protective impact of vincristine against plasma biochemical alteration caused by sustained beta-adrenergic stimulation in male Wistar rat. Animals were randomly divided into four groups; Group 1 served as normal control and was treated with saline (10 mL/kg), Group 2 received isoprenaline (ISO) (1 mg/kg) group daily for 14 days, group 3 was treated with ISO (1 mg/kg) and vincristine (25 µg/kg) simultaneously for 14 days while group 4 was pre-treated with vincristine (25µg/kg) for 14 days before exposure to isoprenaline. All treatment was done intraperitoneal. Following euthanasia, extract plasmas were used for haematological and plasma biochemical assays. Our results showed a significant erythrocytosis, haematocrit, haemoglobinemia and leucocytosis while there was a decreased in lymphocyte and thrombocyte in ISO-treated animals when compared with the control animals. However, VCR pre-treatment reversed these haematological parameters to normal levels. Liver (ALP, AST and ALT) and kidney (Creatinine, BUN, globulin, albumin and total protein) function markers were greatly altered in ISO-treated animals. However, pretreatment with VCR significantly modulated these markers. Plasma electrolytes were also modulated by VCR pre-treatment against the derangement caused by ISO treatment. Finally our study suggest that vincristine pre-treatment protected animals exposed to sustained β-adrenergic stimulation from haematological, liver and kidney function alterations